A razoabilidade e a proporcionalidade como garantias constitucionais na dosimetria da penalidade disciplinar - Campos, Adir Cláudio (2017)
The principles of reasonableness and proportionality are rules of theDemocratic State of Law, and constitute the core of fundamental rights, which in turn revolve around the dignity of the human person and due process of law. In function of this directing force, fulfill the function of conferring structure and consistency to the other principles, indicating the way in which the State and the public administration should operate in the exercise of its coactive function, establishing objective criteria for the general and abstract prediction of the norm to fit the specific case, since the types of infractions described in the disciplinary statutes contain in the main mostly open and indeterminate concepts, requiring the applicator of the norm a balanced and balanced action in the fixation of the penalty of public servants in the administrative disciplinary process. In this sense, criteria such as the duty of fairness, congruence and equivalence, which constitute the triple function of reasonableness; and the adequacy, necessity and proportionality in the strict sense, in the classic tripartition made by the German Constitutional Court, are parameters of remarkable juridical property to solve cases under the command of the norm conceived in its integral rule and principles. This is followed by the concrete examination of the disciplinary types described in article 132 of Law No. 8.112 / 90, where, in both a deductive and an inductive operation, the principles are applied in those cases that give rise to ambiguity of the norm and peculiar situation in which they are decided by the public administration, many of which, object of control of legality by the Judiciary Power.This control proves to be important in a large part of the infractions, but the constitutionality control over the norm that allows the retirement of the public servant to be canceled by illicit ones that are only assessed after the inactivity.As the last topic to be treated, some administrations appear the procedure of suspension of the process by agreement in which it is opportune the extinction of the done with the server that fulfills some requirements. This is a salutary measure, since it has a double effect: pedagogical and optimizing public spending for those processes that are effectively needed to be implemented.